Race in the age of Obama. Part 2 - Cunnigen, Donald; Bruce, Marino A. (Marino Anton) (Bingley, U.K. : Emerald, 2015)
This volume is the second part of a two volume examination of the sociological and cultural impact derivative of Barack Hussein Obama's initial election and re-election as President of the United States. For some scholars and political pundits, the election of the first African-American president was thought to be the start of a post-racial era in the United States. His election/re-election has created a new racial dynamic within the nation. The Obama administration has faced unprecedented political challenges that have led to the deepening of racial divisions and a crystallization of multiple inequities within the country. The editors envision a volume highlighting a number of sociological themes within the following five primary foci: 1) an examination of the 2012 election; 2) the intersection of racial politics with new conservative and voting rights issues; 3) the intersection of race and class with sociocultural issues; 4) an examination of the international perspective of the Obama administration in relationship to the African Diaspora; and 5) an exploration of the potential for multiracial coalitions and social movements to bring about positive structural change.
Sociologists for Obama : scholarly activism in a presidential campaign / Donald Cunnigen, Robert Newby -- The race problematic in the age of Barack Obama / Rickey Hill -- LGBT politics and rights through the Obama era : President Barack Obama's evolution on LGBT issues / Ravi K. Perry, Joseph P. McCormick II -- Racial justice under President Obama : a misuse of the bully pulpit / Bertin M. Louis, Jr., Wornie L. Reed -- "This brother needs prayer" : an insider's critique on religion, race and President Obama's support of marriage equality / D. Mark Wilson -- Life at the edge : precarity and economic insecurity in the Obama era / Cedric Herring, Hayward Derrick Horton, Melvin Thomas -- Understanding the parent PLUS loan debate in the context of black families / Awilda Rodriguez -- The racial framing of the Barack Obama presidency : a mixed methods analysis of HBCU student perceptions / Bruce H. Wade, Sinead Younge -- US Africa policy in the age of Obama : change and continuity in global hegemony / Choolwe Beyani -- From reel to real : Hollywood representations of black presidents and reactions to the Obama presidency / Yvonne D. Newsome.
Print version record
Keywords: Social Science -- Discrimination & Race Relations; Sociology; Ethnic minorities & multicultural studies; Race relations; Ethnic relations; United States -- Race relations